(untitled) (Physical Sciences and Technology, 2017)
We make theoretical analysis of bound and resonance states of 8Li and 8B nuclei. The analysis is carried out within a three-cluster microscopic model which account for polarizability of interacting clusters. Main attention is paid to the nature of resonances states embedded in two-cluster continuum. We also study effects of the cluster polarization on the spectrum of bound and resonance states, and on the elastic and inelastic n + 7Li and p+ 7Be scattering.